2010
DOI: 10.1002/eji.200939566
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of collagen‐induced arthritis by Natura‐α via regulation of Th‐1/Th‐17 responses

Abstract: Cytokines and CD41 Th cells play a crucial role in the pathogenesis of rheumatoid arthritis. Among the Th populations, Th-1 and Th-17 have been described as pathogenic in collagen-induced arthritis (CIA) whereas Th-2 and Treg were found to have protective effects. The objective of this study was to examine the affect of Natura-a, a newly developed cytokine regulator, on CIA and on Th cell development. Natura-a treatment was administered before or during arthritis induction. Anti-type II collagen antibodies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Natura-alpha has anti-proliferative and anti-inflammatory activities both in vitro and in vivo via inhibition of CDKs and pro-inflammatory cytokines (16, 32). In this study, our data showed that Natura-alpha inhibited growth of prostate cancer cells LNCaP, LNCaP-AI, PC3, and DU145 by MTT and anchorage independent assay.…”
Section: Discussionmentioning
confidence: 99%
“…Natura-alpha has anti-proliferative and anti-inflammatory activities both in vitro and in vivo via inhibition of CDKs and pro-inflammatory cytokines (16, 32). In this study, our data showed that Natura-alpha inhibited growth of prostate cancer cells LNCaP, LNCaP-AI, PC3, and DU145 by MTT and anchorage independent assay.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Th17 cells has recently emerged as pivotal in several models of autoimmune and inflammatory diseases (40). Our results suggest that Th17 cells could contribute to both intestinal and joint inflammation in the B27‐transgenic rat model of SpA.…”
Section: Discussionmentioning
confidence: 99%
“…and a clinical score based on disease severity was given for each mouse. Clinical assessment was performed two to three times per week, for up to 60 days in C57/BL6 mice and 35 days in DBA/1 mice as previously described [ 32 ]. Briefly, the date of disease onset was recorded, and the clinical severity of each joint or group of joints (toes, tarsus, ankle, wrist and fingers) was graded as follows: 0 (normal), 1 (swelling or focal redness of finger joints), 2 (mild swelling), 3 (severe swelling) or 4 (necrosis).…”
Section: Methodsmentioning
confidence: 99%